Association of hypertension with risk factors using logistic regression - Mustafa, Mamat; Wan Muhamad Amir, Wan Ahmad; Mohamad Arif, Awang Nawi (2014)
Hypertension is one of the important public health challenges worldwide because of its high frequency and concomitant risks of cardiovascular and kidney disease. A hypertension model is built to test the interaction and significance between the factors. In this present paper, we present the results that gained from multiple logistic regression method and used to model the relationship between the ordinal outcome variable. The significant variables is chosen based on the p-value associated to the significant level of model that lies on α = 0.05. Logit determination and the correlation between the variables are also discussed for further analysis. there are three factors that most significant of the six factors tested were identified as having influence significantly the performance of human blood pressure (hypertension). These factors are age (p-value <0.000), body mass index (p-value <0.001) and systolic (p-value <0.001). The use of mathematical software PASW version 18 is applied in this research as an alternatives calculation procedures derived from the methodology.